Pengaruh Kemampuan, Keterlibatan, Dukungan Manajemen Puncak, Kualitas Sistem Informasi, Dan Kualitas Informasi Terhadap Kinerja Pengguna Sistem Informasi Akuntansi Pada Organisasi Sektor Publik Di Kabupaten Blora - Yulianto, Denny, Dr. Erma Setyawati, Akt., MM (2016)
This study aims to analyze the effect of users ability, users involvement, top management support, information system quality, and information quality on user performance of the accounting information system. The sample of this study are 97 employees of Public Service in Blora Regency taken by area probability sampling. Collecting data using questionnaire techniques. Data were analyzed using multiple linear regression analysis. Regression results were tested with the classical assumption method, consisting of multicolinierity test, autocorrelation test, heteroscedasticity test, and test for normality. Conclusion any hypothesis testing results show that (1) users ability, information system quality, and information quality have a significant effect on user performance of accounting information system; (2) users involvement and top management support have no significant effect on user performance of accounting information system.